Role of laccase and xylanase, with or without ferulic acid esterase-producing Lactiplantibacillus plantarum, on the aerobic stability, microbial composition and in vitro degradability of mulberry silage - Ya Su; Qiang Yu; Yulong Xi; Yuanjiang Rong; Yixi Long; Yixiao Xie; Hong Sun; Jun Hao; Fuyu Yang; Yulong Zheng (BMC Microbiology)
Abstract Laccase (L), xylanase (X), and ferulic acid esterase (FAE) act on lignin - carbohydrate complexes. Whether these enzymes, alone or combined, can improve mulberry ensiling and aerobic stability is unclear. This study assessed the effects of L, X, and FAE - producing L. plantarum (LP) on whole - plant mulberry silage’s fermentation quality, aerobic stability, and microbial communities during aerobic exposure. After 60 days of ensiling, mulberry silage treated with CK, LP, LX, or M was unsealed for 1, 3, 5, or 7 days for exposure to air. The results indicated that the LP and M treatments decreased mulberry silage pH. The lower aminopeptidase and carboxypeptidase activities in the LP and M treatments might have contributed to the reduced degradation of crude protein (CP) and ammoniacal nitrogen (NH3-N) content (P < 0.05). Compared with the CK treatment, the addition of LX and M increased the acetic acid (AA) content by 1.49-2.68-fold, indicating greater aerobic stability (P < 0.05), which contributed to maintaining the storage quality of the silages during aerobic exposure. The application of additives to mulberry silage reduced the species richness; specifically, the additive treatments led to an increase in the relative abundance of Kondoa and Lentilactobacillus while decreasing that of Enterococcus and Delftia. Notably, Lentilactobacillus exhibited the capacity to inhibit the growth of other harmful microorganisms and emerged as the dominant genus within the LX group. In conclusion, treatment with the combination of laccase, xylanase, and FAE-producing L. plantarum can serve as an effective method to improve the silage quality and aerobic stability of mulberry.